CONTAINER RENTAL SYS TEM ON PT. PUTRA LINTAS KEMAS - Achmad Yani; Hariyanto, SKom, MMSI Hariyanto, SKom, MMSI (Jurnal Sistem Informasi, 1998)
With existence of computerized system within a company can generate reports with a faster time, by saving time, generate more accurate reports, and provides convenience in data searching process again if needed at any time. In addition the use of computer application programs and system design, providing greater benefits compared with manual recording.